2000
DOI: 10.1002/1521-3935(20001201)201:18<2765::aid-macp2765>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of scratch and abrasion resistant polymeric nanocomposites by monomer grafting onto nanoparticles, 2 Characterization of radiation-cured polymeric nanocomposites

Abstract: By in situ grafting methacroyloxy functionalized silanes on commercial nanoglobular silica polymerization‐active silico‐organic nanoparticles were prepared. In radiation (UV, EB) induced polymerization reactions these modified nanoparticles form covalent crosslinks to acrylate substrates, thus efficiently modifying their viscoelastic properties. The transparent nanopowder composites can be used as scratch resistant coatings. The composite films show excellent adhesion on PC and PVC and good abrasion resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
62
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 97 publications
(63 citation statements)
references
References 3 publications
0
62
0
1
Order By: Relevance
“…Thus, in order to Figure 1. 4 Schematic structure of grafted silica nanoparticles and radiation-cured grafted silica/acrylate networks (adapted from reference [41]). …”
Section: Scratch-and Abrasion-resistant Coatingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, in order to Figure 1. 4 Schematic structure of grafted silica nanoparticles and radiation-cured grafted silica/acrylate networks (adapted from reference [41]). …”
Section: Scratch-and Abrasion-resistant Coatingsmentioning
confidence: 99%
“…Recent advances in nanotechnology plays an important role in the development of scratch-resistant coatings [39,40]. Gläsel et al have shown the use of siloxane-encapsulated SiO 2 nanoparticles to develop scratch-and abrasion-resistant coatings [41,42] (Fig. 1.4).…”
Section: Scratch-and Abrasion-resistant Coatingsmentioning
confidence: 99%
“…[17][18][19] The mixture was sonicated for 2 h. The modified silica (A-Silica) was separated using a centrifuge and dried at 50 C under vaccum for 6 h.…”
Section: Surface Modification Of Nano-silicamentioning
confidence: 99%
“…For the modified silica nanoparticles, two additional peaks are found at À57:6 and À68:6 ppm. 18,19 Figure 1c shows a 13 C NMR spectrum of neat APTS (dissolved in CDCl 3 ) and Figure 1d shows a 13 C CP MAS NMR spectrum of A-Silica. In Figure 1d, three peaks were observed around 9.8, 24.5 and 45.9 ppm, which could be assigned to C1 0 , C2 0 and C3 0 .…”
Section: Silanation Of Silicamentioning
confidence: 99%
“…Presently, most inorganic fillers are either close to spherical or composed of small platelets [11]. In order to achieve a significant improvement in scratch resistance, nanoparticles are usually added at a weight fraction in the range of 20% or more [12][13][14][15]. While the mechanism by which nanoparticles improve hardness is under debate, it is clear that nanoparticles must make up a significant fraction of the overall volume in order to be mechanically active.…”
Section: Introductionmentioning
confidence: 99%